Acidentes de trabalho com exposição a material biológico no Brasil: qualidade de informações, tendência temporal e distribuição espacial - GOMES, Sâmea Cristina Santos (2019)
Introduction: Accidents at work with exposure to biological material (ATEMB) are characterized as bodily injuries involving direct contact with blood and organic fluids in the work environment, affecting mainly health professionals. Objective: To analyze the data quality in the information system, the epidemiological profile of the cases, and the spatialtemporal distribution of the ATEMB among health professionals in Brazil. Methods: This is an ecological study carried out with all the cases of ATEMB in health professionals notified in the Notification of Injury Information System (SINAN) in the period 2010-2016. In order to study the quality of the data available in SINAN on the ATEMB, the data quality dimensions that included accessibility, timeliness and completeness were used. A descriptive analysis of the data was carried out in order to study the epidemiological profile of ATEMB cases among health professionals in Brazil, by means of calculations of absolute and percentage frequencies to represent the cases of ATEMB among health professionals. For the study of the temporal analysis, the incidences were calculated for each year in three units of analysis: Brazil, the regions and the Federative Units (UF) being these standardized by the direct method. The Prais- Winsten generalized linear regression model was used to evaluate the growth, decreasing or stable variations from the analysis of the growth measure and the level of significance (p <0.05). For the spatial analysis study, the municipalities were used as the unit of analysis and the incidence was calculated for each year of the study. Gross incidences were adjusted by the local empirical Bayesian model. The Moran Global and Local Indices were calculated to observe the existence of spatial autocorrelation of ATEMB cases and to delimit high and low risk clusters. Statistical analyzes were performed in Stata® software version 14.0 and GeoDa version 1.10. All maps were built in QGIS 3.6.0 software. Results: Article 1: It was verified that the information is accessible and opportune, with lag of the current year in relation to the beginning of the study. SINAN-ATEMB presented a high percentage of incomplete data in the variables: schooling, working time in the occupation, organic material, serological status of the injured and the source patient, adopted behaviors, evolution of the case and issue of the Work Accident Notice ). Article 2: a greater occurrence of these accidents was observed in the female population, in the age group between 25-31 years, with 12 years or more of schooling. Nursing assistants and technicians were the most affected (64.71%); Accident circumstances indicate that blood was the biological material most involved in accidents (74.93%) through the percutaneous route (75.33%), with the needle being the main causative agent (57.59%), 29 , 71% did not wear gloves at the time of the accident. The procedures adopted after the exposure were as recommended by the Ministry of Health, however, 1.12% refused the indicated chemoprophylaxis. Article 3: The highest incidence rate in the country (16.84 accidents per thousand professionals / year) was observed in 2014. In the analysis by region of the country, the highest incidence occurred in the Midwest, South and Southeast regions. In the UF analysis, the highest incidence was found in. There was a stable trend in the incidence rate of ATEMB among health professionals in the country in general. Article 4: ATEMB among health professionals were distributed in a heterogeneous way in the Brazilian municipalities, and this distribution was not random, with high-risk agglomerates mainly in the Center-West, Southeast and South regions of the country and low risk of in the North and Northeast regions. Conclusions: ATEMB disproportionately affects health professionals in Brazil, and the observation of regional inequalities, in order to understand the occurrence of these accidents, exposes the importance of geographic space and social dynamics in the definition of places with capacity to maintain this aggravation. This observation must be taken into account in the organization of strategic actions to reduce the number of work accidents, in the planning of the offer of permanent education in health, generating positive impact in the registry of accidents in the information system, and reducing underreporting of cases.